Longitudinal associations of neighborhood socioeconomic characteristics and alcohol availability on drinking: Results from the Multi-Ethnic Study of Atherosclerosis (MESA). (November 2015) - Brenner, Allison B.; Borrell, Luisa N.; Barrientos-Gutierrez, Tonatiuh; Diez Roux, Ana V.
Abstract: Neighborhood socioeconomic characteristics and alcohol availability may affect alcohol consumption, but adequate longitudinal research to support these hypotheses does not exist. We used data from the Multi-Ethnic Study of Atherosclerosis (MESA) (N = 6163) to examine associations of changes in neighborhood socioeconomic status (SES) and alcohol outlet density, with current, weekly, and heavy daily alcohol consumption in hybrid effects models. We also examined whether these associations were moderated by gender, race/ethnicity, and income. Increases in neighborhood SES were associated with decreases in the probability of current alcohol use after adjustment for age, gender, race/ethnicity, individual SES, marital status and time since baseline [probability ratio (PR) per SD increase in neighborhood SES = 0.96, 95% confidence interval (CI) (0.96.0.99)]. Increases in liquor store densities were associated with increases in weekly alcohol consumption [ratio of weekly drinks per SD increase in outlet density = 1.07, 95% CI (1.01.1.05) for men, PR = 1.11, 95% CI (1.01.1.21) for women]. Relationships between current alcohol use and neighborhood SES and between weekly beer consumption and neighborhood SES were generally stronger among those with higher incomes. Neighborhood socioeconomic context and the availability of alcohol may be important for understanding patterns of alcohol use over time, and for targeting interventions and policies to reduce harmful alcohol use. Highlights: Alcohol use was modeled as a function of neighborhood context. Increases in neighborhood economic status resulted in decreasing alcohol use. Increases in liquor stores resulted in increases in weekly drinking. Relationships between neighborhood and drinking varied by individuals' income.